Tissue-specific Expression and Dynamic Organization of SR Splicing Factors in Arabidopsis - Fang, Yuda (The American Society for Cell Biology, 2004)
The organization of the pre-mRNA splicing machinery has been extensively studied in mammalian and yeast cells and far less is known in living plant cells and different cell types of an intact organism. Here, we report on the expression, organization, and dynamics of pre-mRNA splicing factors (SR33, SR1/atSRp34, and atSRp30) under control of their endogenous promoters in Arabidopsis. Distinct tissue-specific expression patterns were observed, and differences in the distribution of these proteins within nuclei of different cell types were identified. These factors localized in a cell type-dependent speckled pattern as well as being diffusely distributed throughout the nucleoplasm. Electron microscopic analysis has revealed that these speckles correspond to interchromatin granule clusters. Time-lapse microscopy revealed that speckles move within a constrained nuclear space, and their organization is altered during the cell cycle. Fluorescence recovery after photobleaching analysis revealed a rapid exchange rate of splicing factors in nuclear speckles. The dynamic organization of plant speckles is closely related to the transcriptional activity of the cells. The organization and dynamic behavior of speckles in Arabidopsis cell nuclei provides significant insight into understanding the functional compartmentalization of the nucleus and its relationship to chromatin organization within various cell types of a single organism.